Quantifying the survival benefit of completing all the six cycles of radium-223 therapy in patients with castrate-resistant prostate cancer with predominant bone metastases - John Buscombe; Daniel Gillett; Nick Bird; Anne Powell; Sarah Heard; Luigi Aloj (World Journal of Nuclear Medicine)
A retrospective analysis was performed of epidemiological data assessing the survival of patients who had received radium-223 for castrate-resistant metastatic prostate cancer treated at a regional tertiary referral center over a 5-year period. The patients' age, date of first treatment, and the number of cycles of radium-223 given were obtained from the patients' electronic patient record (EPR). Data on the date of death were provided by national death registrations which update the EPR via a unique national health service number. A total of 187 patients (mean age on the date of first treatment: 73 years; range: 56–93) were treated from April 1, 2014, to June 30, 2019. The median overall survival of the 119 patients (71%) who had died by December 31, 2019, was 15 months. There was no significant age difference between those who had died and survivors (72 vs. 74 years). On a further analysis, it was found that the median overall survival of the 107 patients who had received all the six cycles of radium-223 was 31 months, significantly longer than the median overall survival of only 6 months for those eighty patients who had received less than the full course of six cycles of radium-223 (P = 0.001). Of those who received all the six cycles of treatment, 58 patients had died (58%) and the 1-year survival was 87%. This was compared to the group of patients receiving <6 cycles of radium-223 where 61 patients (76%) had died and the 1-year survival was 30%. Therefore, the hazard ratio of dying before 1 year if the patient did not receive all the six cycles of treatment was 2.9. Where the reason for stopping treatment was recorded on the EPR the most common cause for the cessation of treatment was because of the side effects caused by the treatment itself. Other causes were hospitalization with comorbidities, disease progression, or patient choice. Given the survival advantage of receiving the full course of all the six cycles of treatment, this should be administered if possible and the patients should be managed in such a way as to allow the complete treatment course to be given.